A processing technology for PEEK electric wire
Through the combination of modified PEEK resin and functional additives, the segmented cooling and crystallization process, combined with metal plating treatment, the problem of insufficient anti-ultraviolet aging and flame retardant performance of PEEK wires is solved, and the service life and fire resistance of the wires are significantly improved.
Patent Information
- Application Number
- CN202410006118.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-03
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-01-03
AI Technical Summary
The existing PEEK wires have poor UV aging resistance and flame retardant properties, resulting in shortened service life and insufficient fire resistance.
Modified PEEK resin and functional additives are used to coat metal conductors through a single screw extruder, combined with a segmented cooling and crystallization process, to form an excellent insulating layer, and metal plating is performed on the surface of the conductor to improve high temperature resistance and oxidation resistance.
It significantly improves the UV aging resistance and flame retardant performance of PEEK wires, extends the service life, and improves fire resistance, ensuring wire quality and electrical performance.
Smart Images

Figure BDA0004647180180000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electric wire and cable production, in particular to a processing technology for a PEEK electric wire. Background Art
[0002] Wires are composed of one or more soft conductors, which are covered with a soft sheath; cables are composed of one or more insulated conductors, which are covered with a tough outer layer of metal or rubber. Cables and wires are generally composed of three parts: core wire, insulating sheath and protective sheath. In daily habits, people call household wires wires and power cables cables. Wires and cables mainly include bare wires, winding wires, power cables, communication cables and optical cables, and electrical equipment.
[0003] A method for preparing a PEEK insulated wire is disclosed in a patent document with application number "CN202311144635.4", which includes the following steps: (1) vacuum sputtering a metal wire to form a rough surface of the metal wire; (2) extruding a PEEK resin material and wrapping it on the surface of the metal wire to form a PEEK resin insulation layer, and cooling to obtain the PEEK insulated wire. The PEEK insulated wire prepared by this method has good bonding between the PEEK material and the metal wire, which can prevent the PEEK insulated wire from cracking and falling off during use.
[0004] Although the PEEK insulated wire prepared in the above patent document has good insulation performance, its own anti-ultraviolet aging performance is relatively poor. If the PEEK wire is exposed to sunlight for a long time, it will age to varying degrees, thereby shortening its service life. Furthermore, although it also has good flame retardant properties, its flame retardant properties still need to be further improved or enhanced to ensure its quality. Therefore, the present application provides a processing technology for PEEK wires to solve the above-mentioned technical problems. Summary of the invention
[0005] The purpose of the present invention is to provide a processing technology for PEEK electric wires. The PEEK electric wires produced by the present invention not only have good anti-ultraviolet aging performance, but also extend the service life of the PEEK electric wires to a certain extent. Furthermore, they also have excellent flame retardant properties, significantly improve the fireproof performance of the PEEK electric wires, and effectively ensure their quality.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A processing technology for PEEK electric wire comprises the following steps:
[0008] S1. Clean the PEEK insulating material, transfer the cleaned PEEK insulating material into a drying device, and dry it at a temperature of 140 to 180° C. for 4 to 12 hours; after drying, store it for future use;
[0009] S2. The prepared oxygen-free copper rod with a diameter of 8.0 to 16.0 mm is subjected to wire drawing, annealing and electroplating treatment in sequence; wherein the deformation rate of the conductor wire drawing is 30 to 99%; and the annealing temperature is 380 to 480° C.;
[0010] S3, preheating the metal wire treated in step S2 at a temperature of 160-250° C., and after the preheating is completed, heating and melting the dried modified PEEK resin, and then extruding it through a single-screw extruder to evenly coat the surface of the metal wire to form a PEEK resin insulation layer;
[0011] The modified PEEK resin is made of the following raw materials in parts by weight: 90 to 110 parts of polyetheretherketone resin, 50 to 65 parts of low-density polyethylene, 6 to 10 parts of functional additives, 2 to 3 parts of tricresyl phosphate, 8 to 12 parts of talc, 10 to 15 parts of nano-cerium dioxide, 8 to 15 parts of polyethylene wax, and 6 to 12 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]; the low-density polyethylene is selected from TN26 low-density polyethylene, and its melt index is 2.5 to 4.0 g / 10 min;
[0012] The functional additive is prepared by using porous carrier microspheres composed of nano zirconium dioxide and cerium dioxide as starting materials, pre-treated with a silane coupling agent, and then effectively encapsulating 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and 2-hydroxy-4-n-octyloxybenzophenone retained on the surface of the porous carrier microspheres and in their pore structures through a modifier and a grafting agent grafted on the surface, thereby finally preparing the functional additive;
[0013] S4, the wire blank obtained after the treatment in step S3 is subjected to segmented cooling and crystallization; wherein the specific process of segmented cooling and crystallization is as follows: first, the wire blank obtained after the treatment in step S3 is placed in a heat-insulating cotton casing with a length of 1.0 to 1.2 m for heat preservation treatment, wherein the temperature in the tube is maintained at 100 to 150° C.; secondly, the remaining wire blank is cooled and crystallized in hot water with a temperature of 80 to 90° C., and the cooling length is 1.5 to 2.5 m; then, the wire blank is cooled and crystallized in hot water with a temperature of 50 to 60° C., and the cooling length is 1.5 to 2.5 m; finally, the wire blank is cooled and crystallized at room temperature, and the cooling length is 3 to 5 m;
[0014] S5. After cooling is completed, the wire is taken up, and the final product is the PEEK wire product.
[0015] Furthermore, the preparation method of the functional additive comprises the following steps:
[0016] Step 1, uniformly dispersing the pretreated carrier microspheres in N, N-dimethylformamide at a solid-liquid ratio of 0.008-0.015 g / mL, and then adding a grafting agent with a volume of 0.5-0.8 times and a reaction accelerator with a mass of 8-15% of the grafting agent to the obtained mixed components; after mixing and stirring evenly, stirring and reacting under nitrogen protection until no irritating odor escapes; then filtering the obtained product components, washing the obtained filter cakes with N, N-dimethylformamide and ethanol for 3-4 times respectively, and finally drying them, and storing the obtained solid micropowder for standby use;
[0017] Step 2: Add the solid micropowder into a mixed solvent at a solid-liquid ratio of 0.02 to 0.05 g / mL, and after ultrasonic dispersion for 20 to 30 minutes, add a modifier with a mass of 0.6 to 1.0 times that of the functional additive, mix and stir evenly, and then keep the mixture at a temperature of 45 to 50° C. for 10 to 20 hours; after the reaction is completed, centrifuge the resulting components, wash the resulting filter cake with acetone for 2 to 3 times, and then vacuum dry it to obtain the functional additive.
[0018] Furthermore, the preparation method of the pretreatment carrier microspheres is: the inorganic carrier microspheres are uniformly dispersed in N, N-dimethylformamide at a solid-liquid ratio of 0.01 to 0.02 g / mL, and then γ-aminopropyltrimethoxysilane is added thereto with a mass of 0.6 to 1.0 times that of the inorganic carrier microspheres, the mixture is stirred evenly, and then refluxed and stirred for 20 to 30 hours; after the reaction is completed, the product group is separated from the solid and liquid, and the obtained filter cake is washed with toluene and ethanol for 3 to 4 times respectively, and finally it is vacuum dried at 80 to 90°C to obtain the pretreatment carrier microspheres.
[0019] Furthermore, the preparation method of the grafting agent is: adding o-hydroxybenzoic acid to dichlorothionyl at a solid-liquid ratio of 0.01 to 0.03 g / mL, reflux reaction until no irritating odor escapes, and then distilling off the remaining dichlorothionyl in the resulting component to obtain the grafting agent.
[0020] Furthermore, the preparation method of the modifier is: adding formic acid aldehyde and carbon amide into deionized water at a mass ratio of 1:3 to 5:8 to 12 while stirring, adjusting the pH to 8.8 to 9.2 after mixing and stirring evenly; then keeping warm and reacting at a temperature of 38 to 42°C for 2 to 4 hours; after the reaction is completed, adjusting the pH of the resulting component to 2.8 to 3.2, and adding potassium phosphate with a mass of 0.6 to 0.8 times that of carbon amide, mixing and stirring evenly, keeping warm and stirring the reaction at a temperature of 20 to 30°C for 1 to 2 hours, and after the reaction is completed, drying it at a temperature of 125 to 135°C for 3 to 5 hours, and the final result is the modifier.
[0021] Furthermore, the preparation method of the mixed solvent is: deionized water and dimethyl sulfoxide are mixed and stirred evenly in a volume ratio of 1:3-5, and then 2-3.5% by weight of coconut oil fatty acid monoethanolamide, 3-5% by weight of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, and 0.6-1.2% by weight of 2-hydroxy-4-n-octyloxybenzophenone are added thereto respectively, and after ultrasonic dispersion, the obtained product is the mixed solvent.
[0022] Furthermore, the coating material is selected from any one of metal nickel, metal cadmium and metal chromium; and the coating thickness is 0.003-0.015 mm.
[0023] Furthermore, the reaction accelerator is selected from any one of N,N-diethylethylamine and benzopyridine.
[0024] Furthermore, the preparation method of the carrier microspheres is as follows: 0.5-0.7 g / mL of zirconium oxynitrate aqueous solution and 0.2-0.3 g / mL of cerium ammonium nitrate aqueous solution are mixed at a volume ratio of 1-2:1, and then polymethyl methacrylate microspheres with a mass 1-3 times that of zirconium oxynitrate and anhydrous ethanol with an equal volume to the zirconium oxynitrate aqueous solution are added thereto in sequence, and after ultrasonic dispersion until there are no obvious large solid particles, the mixture is heat-treated at a temperature of 80-110°C for 10-20 hours; after the treatment is completed, the obtained solid product is placed in a high-temperature calcination device, the calcination temperature is increased to 550-650°C at a rate of 5-10°C / min, and the solid product is high-temperature calcined at this temperature for 8-15 hours; finally, the calcined solid product is naturally cooled to room temperature, and the obtained carrier microspheres are obtained.
[0025] Furthermore, the particle size of the polymethyl methacrylate microspheres is 2 to 5 μm, the pore size is 20 to 60 nm, and the cross-linking degree is 30 to 80%.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. In the present invention, porous carrier microspheres composed of zirconium dioxide and cerium dioxide are used as raw materials, and are pretreated by γ-aminopropyltrimethoxysilane to obtain pretreated carrier microspheres. The pretreated carrier microspheres are then ultrasonically dispersed in N,N-dimethylformamide, and a grafting agent is added thereto. Under the action of a reaction accelerator, the grafting agent reacts chemically with the relevant groups on the surface of the pretreated carrier microspheres, and finally the grafting agent with excellent anti-ultraviolet performance is grafted on the surface of the pretreated carrier microspheres and in the pores of their porous structure, thereby effectively improving the anti-ultraviolet ability of the carrier microspheres. Then the prepared solid micropowder is put into a mixed solvent, and 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and 2-hydroxy-4-n-octyloxybenzophenone are uniformly dispersed on the surface of the solid micropowder and in its pore structure by ultrasonic dispersion, and then a functional additive is added. After the heat preservation reaction, the functional additive reacts chemically with the amino groups remaining on the surface of the solid micropowder through chemical bonds, and is successfully bonded to the surface of the solid micropowder and in its pore structure. Finally, under the combined envelopment of the three-dimensional enveloping layer formed by the grafting agent and the functional additive, the 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and 2-hydroxy-4-n-octyloxybenzophenone retained on the surface of the solid micropowder and in its internal pores are effectively fixed, and the anti-ultraviolet aging performance and flame retardant performance of the functional additive are significantly improved. The functional additive is used as a raw material for processing PEEK wires to further improve its flame retardant performance and aging resistance, effectively prolong its service life, and also improve its fire resistance, and effectively ensure its quality.
[0028] 2. The inner layer of conventional PEEK wire extrusion products will be coated with a layer of high-temperature organic insulation for anti-oxidation treatment due to the high-temperature oxidation of the conductor. The temperature level of this organic insulation layer is generally 220-240°C, and the bilateral insulation thickness is controlled at 0.02-0.04mm, which does not contribute much to the electrical performance. It is calculated based on the typical insulation thickness of the wire of 0.30mm, but accounts for about 10-15% of the overall insulation thickness. The PEEK material itself has a temperature resistance level of 260°C. Due to the low temperature level of the inner insulation, the overall temperature level of the wire cannot reach 260°C, so the finished wire cannot be stably operated at 260°C for a long time. In the present invention, the surface of the conductor adopts a metal coating, which has the effect of high temperature resistance and oxidation resistance. In the conductor preheating section, due to the protective effect of the coating, the conductor will not oxidize. At the same time, the overall coating thickness is 0.003-0.015mm, calculated based on the typical insulation thickness of the wire of 0.30mm, accounting for <5% of the insulation layer. Under the premise of the same wire shape, the effective insulation layer can be increased by more than 5%, which provides effective guarantee for improving electrical performance. Due to the presence of the metal coating, the temperature level of the entire insulation layer of the wire can reach 260°C, effectively improving the temperature resistance of the wire. Furthermore, the segmented cooling crystallization method used in the present invention can effectively prevent the insulation from cooling suddenly after the wire leaves the machine head, causing uneven insulation crystallization and affecting mechanical properties, thereby ensuring the quality of the PEEK wire. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] A processing technology for PEEK electric wire comprises the following steps:
[0032] S1. Clean the PEEK insulating material, transfer the cleaned PEEK insulating material into a drying device, and dry it at 140° C. for 4 hours; after drying, store it for future use;
[0033] S2. The prepared oxygen-free copper rod with a diameter of 8.0 mm is subjected to wire drawing, annealing and electroplating treatment in sequence; wherein the deformation rate of the conductor wire drawing is 30%; the annealing temperature is 380°C; the plating material is nickel metal, and the plating thickness is 0.003;
[0034] S3, preheating the metal wire treated in step S2 at a temperature of 160° C., and after the preheating is completed, heating and melting the dried modified PEEK resin, and then extruding it through a single-screw extruder to evenly coat the surface of the metal wire to form a PEEK resin insulation layer;
[0035] The modified PEEK resin is made of the following raw materials in parts by weight: 90 parts of polyetheretherketone resin, 50 parts of low-density polyethylene, 6 parts of functional additives, 2 parts of tricresyl phosphate, 8 parts of talc, 10 parts of nano-cerium dioxide, 8 parts of polyethylene wax, and 6 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;
[0036] The functional additive is a porous carrier microsphere composed of nano zirconium dioxide and cerium dioxide as a starting material, which is pretreated with a silane coupling agent, and then the 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and 2-hydroxy-4-n-octyloxybenzophenone retained on the surface of the porous carrier microsphere and in its pore structure are effectively encapsulated by a modifier and a grafting agent grafted on the surface, so as to finally prepare the functional additive;
[0037] S4, the wire blank obtained after the treatment in step S3 is subjected to segmented cooling and crystallization; wherein the specific process of segmented cooling and crystallization is as follows: first, the wire blank obtained after the treatment in step S3 is placed in a 1.0m long insulation cotton casing for insulation treatment, wherein the temperature in the casing is maintained at 100°C; secondly, the remaining wire blank is cooled and crystallized in hot water at a temperature of 80°C, and the cooling length is 1.5m; then, the wire blank is cooled and crystallized in hot water at a temperature of 50°C, and the cooling length is 1.5m; finally, the wire blank is cooled and crystallized at room temperature, and the cooling length is 3m;
[0038] S5. After cooling is completed, the wire is taken up, and the final product is the PEEK wire product.
[0039] The preparation method of the functional additive comprises the following steps:
[0040] Step 1, the pretreated carrier microspheres are uniformly dispersed in N, N-dimethylformamide at a solid-liquid ratio of 0.008 g / mL, and then 0.5 times the volume of the grafting agent and 8% of the mass of the grafting agent are added to the obtained mixed components; after mixing and stirring evenly, stirring and reacting under nitrogen protection until no irritating odor escapes; then filtering the obtained product components, washing the obtained filter cakes with N, N-dimethylformamide and ethanol for 3 times respectively, and finally drying them, and the obtained solid micropowders are stored for standby use;
[0041] Step 2: Add the solid micropowder into a mixed solvent at a solid-liquid ratio of 0.02 g / mL, and after ultrasonic dispersion for 20 minutes, add a modifier with a mass 0.6 times that of the functional additive, mix and stir evenly, and keep the mixture at 45°C for 10 hours; after the reaction is completed, centrifuge the resulting components, wash the filter cake twice with acetone, and then vacuum dry it to obtain the functional additive.
[0042] The preparation method of pretreatment carrier microspheres is as follows: the inorganic carrier microspheres are uniformly dispersed in N,N-dimethylformamide at a solid-liquid ratio of 0.01 g / mL, and then γ-aminopropyltrimethoxysilane with a mass 0.6 times that of the inorganic carrier microspheres is added thereto, the mixture is mixed and stirred evenly, and then refluxed and stirred for reaction for 20 hours; after the reaction is completed, the product group is separated into solid and liquid, and the obtained filter cake is washed with toluene and ethanol for 3 times respectively, and finally it is vacuum dried at 80°C to obtain the pretreatment carrier microspheres.
[0043] The preparation method of the grafting agent is as follows: adding o-hydroxybenzoic acid to thionyl chloride at a solid-liquid ratio of 0.01 g / mL, reflux reaction until no irritating odor escapes, and then distilling off the remaining thionyl chloride in the resulting component to obtain the grafting agent.
[0044] The preparation method of the modifier is as follows: add formic acid aldehyde and carbon amide into deionized water at a mass ratio of 1:3:8 while stirring, adjust the pH value to 8.8 after mixing and stirring evenly; then keep warm and react at 38°C for 2 hours; after the reaction is completed, adjust the pH value of the resulting component to 2.8, and add potassium phosphate with a mass of 0.6 times that of carbon amide, mix and stir evenly, keep warm and stir and react at 20°C for 1 hour, after the reaction is completed, dry it at 125°C for 3 hours, and the final result is the modifier.
[0045] The preparation method of the mixed solvent is as follows: deionized water and dimethyl sulfoxide are mixed and stirred evenly in a volume ratio of 1:3, and then 2% of coconut oil fatty acid monoethanolamide, 3% of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, and 0.6% of 2-hydroxy-4-n-octyloxybenzophenone are added thereto respectively, and after ultrasonic dispersion, the obtained mixed solvent product is obtained.
[0046] The preparation method of carrier microspheres is as follows: 0.5-0.7 g / mL zirconium oxynitrate aqueous solution and 0.2-0.3 g / mL cerium ammonium nitrate aqueous solution are mixed at a volume ratio of 1-2:1, then polymethyl methacrylate microspheres with a mass of 1-3 times that of zirconium oxynitrate and anhydrous ethanol with an equal volume to the zirconium oxynitrate aqueous solution are added in sequence, ultrasonically dispersed until there are no obvious large solid particles, and then heat-treated at a temperature of 80-110°C for 10-20 hours; after the treatment is completed, the obtained solid product is placed in a high-temperature calcination device, the calcination temperature is increased to 550-650°C at a rate of 5-10°C / min, and the solid product is calcined at this temperature for 8-15 hours; finally, the calcined solid product is naturally cooled to room temperature, and the obtained carrier microspheres are obtained; wherein the particle size of the polymethyl methacrylate microspheres is 2-5 μm, the pore size is 20-60 nm, and the cross-linking degree is 30-80%.
[0047] Example 2
[0048] The processing technology of the PEEK wire provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the modified PEEK resin, the amount of the functional additive and the specific preparation method in this embodiment are different. The specific composition of the modified PEEK resin, the amount of the functional additive and the specific preparation method in this embodiment are as follows:
[0049] The modified PEEK resin is prepared from the following raw materials in parts by weight: 100 parts of polyetheretherketone resin, 60 parts of low-density polyethylene, 8 parts of functional additives, 2.5 parts of tricresyl phosphate, 10 parts of talc, 12 parts of nano-cerium dioxide, 10 parts of polyethylene wax, and 9 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;
[0050] The preparation method of the functional additive comprises the following steps:
[0051] Step 1, the pretreated carrier microspheres are uniformly dispersed in N, N-dimethylformamide at a solid-liquid ratio of 0.012 g / mL, and then the grafting agent with a volume of 0.6 times and benzopyridine with a mass of 12% of the grafting agent are added to the obtained mixed components respectively; after mixing and stirring evenly, stirring and reacting under nitrogen protection until no irritating odor escapes; then filtering the obtained product components, washing the obtained filter cakes with N, N-dimethylformamide and ethanol for 3 times respectively, and finally drying them, and the obtained solid micropowders are stored for standby use;
[0052] Step 2: Add the solid micropowder into a mixed solvent at a solid-liquid ratio of 0.04 g / mL, and after ultrasonic dispersion for 25 minutes, add a modifier with a mass 0.8 times that of the functional additive, mix and stir evenly, and keep the mixture at 50°C for 15 hours; after the reaction is completed, centrifuge the resulting components, wash the filter cake twice with acetone, and then vacuum dry it to obtain the functional additive.
[0053] The preparation method of the pretreatment carrier microspheres is as follows: the inorganic carrier microspheres are uniformly dispersed in N,N-dimethylformamide at a solid-liquid ratio of 0.015 g / mL, and then γ-aminopropyltrimethoxysilane with a mass 0.8 times that of the inorganic carrier microspheres is added thereto, the mixture is mixed and stirred evenly, and then refluxed and stirred for reaction for 25 hours; after the reaction is completed, the product group is separated into solid and liquid, and the obtained filter cake is washed with toluene and ethanol for 3 times respectively, and finally it is vacuum dried at 85°C to obtain the pretreatment carrier microspheres.
[0054] The preparation method of the grafting agent is as follows: adding o-hydroxybenzoic acid to thionyl chloride at a solid-liquid ratio of 0.02 g / mL, reflux reaction until no irritating odor escapes, and then distilling off the remaining thionyl chloride in the resulting component to obtain the grafting agent.
[0055] The preparation method of the modifier is as follows: add formic acid aldehyde and carbon amide into deionized water at a mass ratio of 1:4:10 while stirring, adjust the pH value to 9.0 after mixing and stirring evenly; then keep warm and react at 40°C for 3 hours; after the reaction is completed, adjust the pH value of the resulting component to 3.0, and add potassium phosphate with a mass of 0.7 times that of carbon amide, mix and stir evenly, keep warm and react at 25°C for 1.5 hours, and after the reaction is completed, dry it at 130°C for 4 hours, and the final result is the modifier.
[0056] The preparation method of the mixed solvent is as follows: deionized water and dimethyl sulfoxide are mixed and stirred evenly in a volume ratio of 1:4, and then 3.0% of coconut oil fatty acid monoethanolamide, 4% of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, and 1.0% of 2-hydroxy-4-n-octyloxybenzophenone are added thereto respectively, and after ultrasonic dispersion, the obtained mixed solvent product is obtained.
[0057] Example 3
[0058] The processing technology of the PEEK wire provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the modified PEEK resin, the amount of the functional additive and the specific preparation method in this embodiment are different. The specific composition of the modified PEEK resin, the amount of the functional additive and the specific preparation method in this embodiment are as follows:
[0059] The modified PEEK resin is made of the following raw materials in parts by weight: 110 parts of polyetheretherketone resin, 65 parts of low-density polyethylene, 10 parts of functional additives, 3 parts of tricresyl phosphate, 12 parts of talc, 15 parts of nano-cerium dioxide, 15 parts of polyethylene wax, and 12 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;
[0060] The preparation method of the functional additive comprises the following steps:
[0061] Step 1, the pretreated carrier microspheres are uniformly dispersed in N, N-dimethylformamide at a solid-liquid ratio of 0.015 g / mL, and then 0.8 times the volume of the grafting agent and 15% of the mass of the grafting agent are added to the obtained mixed components; after mixing and stirring evenly, stirring and reacting under nitrogen protection until no irritating odor escapes; then filtering the obtained product components, washing the obtained filter cakes with N, N-dimethylformamide and ethanol for 4 times respectively, and finally drying them, and the obtained solid micropowders are stored for standby use;
[0062] Step 2: Add the solid micropowder into a mixed solvent at a solid-liquid ratio of 0.05 g / mL, and after ultrasonic dispersion for 30 minutes, add a modifier with a mass that is 1.0 times that of the functional additive, mix and stir evenly, and then keep warm at 50°C for 20 hours; after the reaction is completed, centrifuge the resulting components, wash the resulting filter cake with acetone three times, and then vacuum dry it to obtain the functional additive.
[0063] The preparation method of the pretreatment carrier microspheres is as follows: the inorganic carrier microspheres are uniformly dispersed in N,N-dimethylformamide at a solid-liquid ratio of 0.02 g / mL, and then γ-aminopropyltrimethoxysilane is added thereto in an amount 1.0 times the mass of the inorganic carrier microspheres, the mixture is stirred evenly, and then refluxed and stirred for reaction for 30 hours; after the reaction is completed, the product group is separated into solid and liquid, and the obtained filter cake is washed with toluene and ethanol for 4 times respectively, and finally vacuum dried at 90°C to obtain the pretreatment carrier microspheres.
[0064] The preparation method of the grafting agent is as follows: adding o-hydroxybenzoic acid to thionyl chloride at a solid-liquid ratio of 0.03 g / mL, reflux reaction until no irritating odor escapes, and then distilling off the remaining thionyl chloride in the resulting component to obtain the grafting agent.
[0065] The preparation method of the modifier is as follows: add formic acid aldehyde and carbon amide into deionized water at a mass ratio of 1:5:12 while stirring, adjust the pH value to 9.2 after mixing and stirring evenly; then keep warm and react at 42°C for 4 hours; after the reaction is completed, adjust the pH value of the resulting component to 3.2, and add potassium phosphate with a mass of 0.8 times that of carbon amide, mix and stir evenly, keep warm and stir and react at 30°C for 2 hours, and after the reaction is completed, dry it at 135°C for 5 hours, and the final result is the modifier.
[0066] The preparation method of the mixed solvent is as follows: deionized water and dimethyl sulfoxide are mixed and stirred evenly in a volume ratio of 1:5, and then 3.5% of coconut oil fatty acid monoethanolamide, 5% of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, and 1.2% of 2-hydroxy-4-n-octyloxybenzophenone are added thereto respectively, and after uniform ultrasonic dispersion, the obtained mixed solvent product is obtained.
[0067] Comparative Example 1: The difference from Example 1 is that an equal amount of solid micropowder is used to replace the functional additive in this example.
[0068] Comparative Example 2: The difference from Example 1 is that in this example, an equal amount of carrier microspheres are used to replace the functional additives.
[0069] Comparative Example 3: The difference from Example 1 is that the mixed solvent in this example does not contain 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and 2-hydroxy-4-n-octyloxybenzophenone.
[0070] Performance Test:
[0071] The PEEK wire samples provided in Examples 1 to 3 and Comparative Examples 1 to 3 are marked as Examples 1 to 3 and Comparative Examples 1 to 3, respectively; and the relevant properties of the PEEK wires and their PEEK resin insulation layers provided in Examples 1 to 3 and Comparative Examples 1 to 3 are tested; wherein the test results of the various properties of the PEEK wires are recorded in Table 1, and the test results of the various properties of the PEEK resin insulation layers are recorded in Table 2:
[0072] 1. Crystallinity test: DSC is used to test the crystallinity of the PEEK resin insulation layer in each group of PEEK insulated wires; wherein, the heating rate during the test is 10°C / min.
[0073] 2. Bonding strength test: A universal tensile machine is used to test the bonding strength of each group of PEEK resin insulation layer and copper wire. The tensile rate during the test is 100mm / min and the sample length is 20cm. The specific test method is: separate the insulation layer from the copper wire on one side, clamp the copper wire and the insulation layer on the upper and lower clamps respectively for tensile testing, and calculate the average tensile force during the calculation process, which is the bonding strength.
[0074] 3. Insulation performance test: The test method is GB / T11021-2014 Electrical insulation heat resistance and expression method, testing the RTE value (relative heat resistance index). The higher the RTE value, the better the insulation.
[0075] 4. Aging resistance test: The test method is GB11026.1 Electrical insulating materials - Heat resistance - Part 1 - Aging procedures and evaluation of test results. The TI value (temperature index) is tested. The TI value corresponds to the Celsius temperature value at a given time (20,000 hours) on the thermal life diagram of the insulating material. The higher the TI value, the better the aging resistance.
[0076] 5. The test method of limiting oxygen index is carried out in accordance with ISO 4589-2 standard.
[0077] 6. The test methods for tensile strength and elongation at break shall be in accordance with GB / T 1040.1-2018.
[0078] Table 1 shows the performance test data of each group of PEEK wire samples
[0079] Test items Crystallinity / % Binding force / N RTE value(℃) TI value (℃) Example 1 43 9.6 255 257 Example 2 47 9.9 258 260 Example 3 45 9.8 256 253 Comparative Example 1 42 9.3 256 255 Comparative Example 2 44 9.5 254 243 Comparative Example 3 43 9.6 255 252
[0080] Table 2 shows the performance test results of each group of PEEK resin insulation layers
[0081]
[0082] By comparing and analyzing the relevant data in Table 1 and Table 2, it can be seen that the PEEK wire produced by the present invention not only has good anti-ultraviolet aging performance, but also prolongs the service life of the PEEK wire to a certain extent. Furthermore, it also has excellent flame retardant properties, significantly improves the fire resistance of the PEEK wire, and effectively guarantees its quality. This shows that the processing technology of the PEEK wire provided by the present invention has a broader market prospect and is more suitable for promotion.
[0083] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0084] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A processing technology for PEEK wire, characterized in that: The following steps are involved: S1. Clean the PEEK insulating material, transfer the cleaned PEEK insulating material into a drying device, and dry it at a temperature of 140 to 180° C. for 4 to 12 hours; after drying, store it for future use; S2. The prepared oxygen-free copper rod with a diameter of 8.0 to 16.0 mm is subjected to wire drawing, annealing and electroplating treatment in sequence; wherein the deformation rate of the conductor wire drawing is 30 to 99%; and the annealing temperature is 380 to 480°C; S3, preheating the metal wire treated in step S2 at a temperature of 160-250° C., and after the preheating is completed, heating and melting the dried modified PEEK resin, and then extruding it through a single-screw extruder to evenly coat the surface of the metal wire to form a PEEK resin insulation layer; The modified PEEK resin is made of the following raw materials in parts by weight: 90 to 110 parts of polyetheretherketone resin, 50 to 65 parts of low-density polyethylene, 6 to 10 parts of functional additives, 2 to 3 parts of tricresyl phosphate, 8 to 12 parts of talc, 10 to 15 parts of nano-cerium dioxide, 8 to 15 parts of polyethylene wax, and 6 to 12 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; The functional additive is a porous carrier microsphere composed of nano zirconium dioxide and cerium dioxide as a starting material, which is pretreated with a silane coupling agent, and then the 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid and 2-hydroxy-4-n-octyloxybenzophenone retained on the surface of the porous carrier microsphere and in its pore structure are effectively encapsulated by a modifier and a grafting agent grafted on the surface, so as to finally prepare the functional additive; S4, the wire blank obtained after the treatment in step S3 is subjected to segmented cooling and crystallization; wherein the specific process of segmented cooling and crystallization is as follows: first, the wire blank obtained after the treatment in step S3 is placed in a heat-insulating cotton casing with a length of 1.0 to 1.2 m for heat preservation treatment, wherein the temperature in the tube is maintained at 100 to 150° C.; secondly, the remaining wire blank is cooled and crystallized in hot water with a temperature of 80 to 90° C., and the cooling length is 1.5 to 2.5 m; then, the wire blank is cooled and crystallized in hot water with a temperature of 50 to 60° C., and the cooling length is 1.5 to 2.5 m; finally, the wire blank is cooled and crystallized at room temperature, and the cooling length is 3 to 5 m; S5, after cooling is completed, the wire is collected, and the final product is the PEEK wire product; The preparation method of the functional additive comprises the following steps: Step 1, uniformly dispersing the pretreated carrier microspheres in N, N-dimethylformamide at a solid-liquid ratio of 0.008-0.015 g / mL, and then adding a grafting agent of 0.5-0.8 times the volume and a reaction accelerator of 8-15% of the mass of the grafting agent to the obtained mixed components; after mixing and stirring evenly, stirring and reacting under nitrogen protection until no irritating odor escapes; then filtering the obtained product components, washing the obtained filter cakes with N, N-dimethylformamide and ethanol for 3-4 times respectively, and finally drying them, and storing the obtained solid micropowder for standby use; The reaction accelerator is selected from any one of N,N-diethylethylamine and benzopyridine; Step 2: adding the solid micropowder into a mixed solvent at a solid-liquid ratio of 0.02 to 0.05 g / mL, ultrasonically dispersing for 20 to 30 minutes, adding a modifier with a mass of 0.6 to 1.0 times that of the functional additive, mixing and stirring evenly, and then heat-retaining the mixture at a temperature of 45 to 50° C. for 10 to 20 hours; after the reaction is completed, centrifuging the resulting components, washing the resulting filter cake with acetone for 2 to 3 times, and then vacuum drying the resulting filter cake to obtain the functional additive; The preparation method of the pre-treated carrier microspheres is as follows: the inorganic carrier microspheres are uniformly dispersed in N,N-dimethylformamide at a solid-liquid ratio of 0.01 to 0.02 g / mL, and then γ-aminopropyltrimethoxysilane is added thereto with a mass of 0.6 to 1.0 times that of the inorganic carrier microspheres, and the mixture is mixed and stirred evenly, and then refluxed and stirred for reaction for 20 to 30 hours; after the reaction is completed, the product group is solid-liquid separated, and the obtained filter cake is washed with toluene and ethanol for 3 to 4 times respectively, and finally vacuum dried at 80 to 90° C., and the obtained product is the pre-treated carrier microspheres; The preparation method of the grafting agent is as follows: adding o-hydroxybenzoic acid to thionyl chloride at a solid-liquid ratio of 0.01 to 0.03 g / mL, reflux reaction until no irritating odor escapes, and then distilling off the remaining thionyl chloride in the resulting component to obtain the grafting agent; The preparation method of the modifier is as follows: adding formic acid aldehyde and carbon amide into deionized water at a mass ratio of 1:3-5:8-12 while stirring, and adjusting the pH value thereof to 8.8-9.2 after mixing and stirring evenly; then keeping the mixture warm at 38-42°C for reaction for 2-4 hours; after the reaction is completed, adjusting the pH value of the resulting component to 2.8-3.2, adding monopotassium phosphate with a mass of 0.6-0.8 times that of carbon amide, mixing and stirring evenly, keeping the mixture warm at 20-30°C for reaction for 1-2 hours, and after the reaction is completed, drying the mixture at 125-135°C for 3-5 hours, and finally obtaining the modifier; The preparation method of the mixed solvent is as follows: deionized water and dimethyl sulfoxide are mixed and stirred evenly in a volume ratio of 1:3-5, and then 2-3.5% by weight of coconut oil fatty acid monoethanolamide, 3-5% by weight of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, and 0.6-1.2% by weight of 2-hydroxy-4-n-octyloxybenzophenone are added thereto respectively, and after ultrasonic dispersion, the mixed solvent is evenly dispersed to obtain a finished product.
2. The processing technology of a PEEK electric wire according to claim 1, characterized in that: The electroplated coating material is selected from any one of metal nickel, metal cadmium, and metal chromium; and the coating thickness is 0.003-0.015 mm.
3. A processing technology for PEEK electric wire according to claim 1, characterized in that: The preparation method of the carrier microspheres is as follows: 0.5-0.7 g / mL of zirconium oxynitrate aqueous solution and 0.2-0.3 g / mL of cerium ammonium nitrate aqueous solution are mixed at a volume ratio of 1-2:1, and then polymethyl methacrylate microspheres with a mass of 1-3 times that of zirconium oxynitrate and anhydrous ethanol with an equal volume to the zirconium oxynitrate aqueous solution are added thereto in sequence, and after ultrasonic dispersion until no obvious large solid particles are present, the mixture is heat-treated at a temperature of 80-110°C for 10-20 hours; after the treatment is completed, the obtained solid product is placed in a high-temperature calcination device, the calcination temperature is increased to 550-650°C at a rate of 5-10°C / min, and the solid product is high-temperature calcined at this temperature for 8-15 hours; finally, the calcined solid product is naturally cooled to room temperature, and the obtained carrier microspheres are obtained.
4. A processing technology for PEEK electric wire according to claim 3, characterized in that: The particle size of the polymethyl methacrylate microspheres is 2-5 μm, the pore size is 20-60 nm, and the cross-linking degree is 30-80%.
